2015
DOI: 10.1021/acscentsci.5b00327
|View full text |Cite
|
Sign up to set email alerts
|

Doped Semiconductor-Nanocrystal Emitters with Optimal Photoluminescence Decay Dynamics in Microsecond to Millisecond Range: Synthesis and Applications

Abstract: Transition metal doped semiconductor nanocrystals (d-dots) possess fundamentally different emission properties upon photo- or electroexcitation, which render them as unique emitters for special applications. However, in comparison with intrinsic semiconductor nanocrystals, the potential of d-dots has been barely realized, because many of their unique emission properties mostly rely on precise control of their photoluminescence (PL) decay dynamics. Results in this work revealed that it would be possible to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 69 publications
7
118
0
2
Order By: Relevance
“…The small τ 1 and A 2 for 0.025mmol-Mn:AIZS/ZnS NCs could be related to the low Mn level in the hosts. Interestingly, according to the literature [3334], a lower Mn level in host NCs should produce a longer PL lifetime probably because the Mn-Mn distance is long. Such a conflict indicates that the Mn emission with Mn-Mn coupling could be existing but not be the major PL mechanism for the fast decay (corresponding to τ 1 ) in Mn:AIZS/ZnS NCs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The small τ 1 and A 2 for 0.025mmol-Mn:AIZS/ZnS NCs could be related to the low Mn level in the hosts. Interestingly, according to the literature [3334], a lower Mn level in host NCs should produce a longer PL lifetime probably because the Mn-Mn distance is long. Such a conflict indicates that the Mn emission with Mn-Mn coupling could be existing but not be the major PL mechanism for the fast decay (corresponding to τ 1 ) in Mn:AIZS/ZnS NCs.…”
Section: Resultsmentioning
confidence: 98%
“…It is suggested that the lifetimes in the range of tens of microseconds may result from radiative decay through trap states or be related to the emission of Mn dopants (diffused from MnS surface to ZnS shell) with enhanced overlap between 3d and sp host states caused by lattice strain due to the spatial distribution of Mn dopants in host NCs. Other authors reported that the spatial distribution of Mn in ZnSe or ZnS NCs affects the PL decay significantly [3334]. Homogenous Mn dopants in ZnSe or ZnS NCs result in single exponential decay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Keeping the size of the host fixed, Mn content was tuned from 32 to 431 Mn atoms per nanocrystal. [30] Keeping the size of the host fixed, Mn content was tuned from 32 to 431 Mn atoms per nanocrystal.…”
Section: Synthesis Strategies and Optical Properties Of Doped Nanocrymentioning
confidence: 99%
“…Reproducedfrom Ref [30]. b) Schematic representation of doped ZnSe nanocrystals with varying Mn concentration.…”
mentioning
confidence: 99%